Human chondrocytes respond discordantly to the protein encoded by the osteoarthritis susceptibility gene GDF5. - Madhushika Ratnayake; Frank Plöger; Mauro Santibanez-Koref; John Loughlin (PLoS ONE, 2014)
A genetic deficit mediated by SNP rs143383 that leads to reduced expression of GDF5 is strongly associated with large-joint osteoarthritis. We speculated that this deficit could be attenuated by the application of exogenous GDF5 protein and as a first step we have assessed what effect such application has on primary osteoarthritis chondrocyte gene expression. Chondrocytes harvested from cartilage of osteoarthritic patients who had undergone joint replacement were cultured with wildtype recombinant mouse and human GDF5 protein. We also studied variants of GDF5, one that has a higher affinity for the receptor BMPR-IA and one that is insensitive to the GDF5 antagonist noggin. As a positive control, chondrocytes were treated with TGF-β1. Chondrocytes were cultured in monolayer and micromass and the expression of genes coding for catabolic and anabolic proteins of cartilage were measured by quantitative PCR. The expression of the GDF5 receptor genes and the presence of their protein products was confirmed and the ability of GDF5 signal to translocate to the nucleus was demonstrated by the activation of a luciferase reporter construct. The capacity of GDF5 to elicit an intracellular signal in chondrocytes was demonstrated by the phosphorylation of intracellular Smads. Chondrocytes cultured with TGF-β1 demonstrated a consistent down regulation of MMP1, MMP13 and a consistent upregulation of TIMP1 and COL2A1 with both culture techniques. In contrast, chondrocytes cultured with wildtype GDF5, or its variants, did not show any consistent response, irrespective of the culture technique used. Our results show that osteoarthritis chondrocytes do not respond in a predictable manner to culture with exogenous GDF5. This may be a cause or a consequence of the osteoarthritis disease process and will need to be surmounted if treatment with exogenous GDF5 is to be advanced as a potential means to overcome the genetic deficit conferring osteoarthritis susceptibility at this gene.